The intermedia agenda setting of interpersonal violence cases in the Malaysian mainstream online news, independent news portal and social media - Norizzati Saifuddin,; Hasmah Zanuddin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Media plays an important role in illustrating the issue of interpersonal violence. Online media such as news portals and social media platforms are highly used in spreading the information virtually and digitally. However, the issue of interpersonal violence is still growing and has recently shown a significant spike. There are not many studies analyzing the exchange of information between these platforms digitally due to online news portals, which are operated by traditional media, and social media being treated as different entities. Yet, real-time posting may lead to an exchange of contents as they follow each other's agenda. A study on intermedia agenda-setting (IAS) - through issues published, agenda-setter, and sentiment - will enable us to understand how agenda setting plays a role in illustrating the issue of interpersonal violence. A content analysis study was conducted on six selected online media, consisting of mainstream and independent news portals and social media. A total of 815 samples of online news, articles and social media postings from five distinct issues were extracted to investigate the content and every 40 relevant comments from each news item were selected to identify how public opinion the portrayal of the issue in these selected online media. In-depth interview was conducted to eight field experts to gain clarification of the result from the content analysis study. Chi-square analysis on three hypotheses were significantly associated. Results revealed that public officials played a major role as the agenda setter. The Star which represents mainstream online news led in setting the agenda on interpersonal violence issues while Facebook which represents social media followed next in setting the agenda. During the process of intermedia agenda-setting, negative sentiments were hugely expressed and exchanged which indicated the uneasiness, feeling disturbed and dissatisfaction on the interpersonal violence cases, which in the end resulted in the sharing and exchanging of news between mainstream news portals and social media. The agenda on social media was set by the public. This confirmed the effects of the flow of elite--non-elite-elite on IAS. Hence, this study contributed to the understanding of the agenda pattern used that also coexisted in different types of media which were created through the intermedia process.